2018
DOI: 10.5539/mas.v12n11p309
|View full text |Cite
|
Sign up to set email alerts
|

ARIMA Model in Predicting Banking Stock Market Data

Abstract: Banking time series forecasting gains a main rule in finance and economics which has encouraged the researchers to introduce a fit models in forecasting accuracy. In this paper, the researchers present the advantages of the autoregressive integrated moving average (ARIMA) model forecasting accuracy. Banking data from Amman stock market (ASE) in Jordan was selected as a tool to show the ability of ARIMA in forecasting banking data. Therefore, Daily data from 1993 until 2017 is used for this study. As a result t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 12 publications
0
35
0
4
Order By: Relevance
“…A time series follows the auto regressive-moving average (ARMA) model if : where and and prefers to auto-regressive part (AR), moving average part (MA), and white noise respectively [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A time series follows the auto regressive-moving average (ARMA) model if : where and and prefers to auto-regressive part (AR), moving average part (MA), and white noise respectively [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The auto-regressive integrated moving average (ARIMA) models are an extension of the ARMA models which is presented by the symbol ARIMA(p, d, q) and it is expressed as follows : where denote orders of auto-regression, q is the order of moving average and d is the number of differencing times. If 0 then the ARIMA model becomes to ARMA model [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wadi et al [1] found the best-fit ARIMA model for forecasting the closed price of Jordan's ASE, with p, d, and q parameters of 2, 1, and 1 correspondingly, and RMSE=4 . For the banking stock data of Jordan's ASE, the ARIMA p=1, d=1, and q=2 suited most with RMSE=1.4 Almasarweh and Alwadi [2]. While forecasting the trucking prices in the US, Miller [3] found that the ARIMA with p=1, d=1, and q=0 best fitted to forecast the Truckload.BLS data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parametric models, such as Autoregressive Integrated Moving Average (ARIMA) and Autoregressive Conditional Heteroskedasticity (ARCH), have been used in various financial sectors. In particular, both the work of [5] and [6] applied ARIMA model in making prediction on banking stock market data and Chinese manufacturing industry. Yunus et al [7] use ARIMA model to capture time correlation and offer possibility distribution of collection records for determined wind-pace time.…”
Section: A Machine Learning Approachesmentioning
confidence: 99%